A positive electrode active material precursor, a method for manufacturing the same, a positive electrode active material, a secondary battery, and a power-driven device
Patent Information
- Application Number
- CN202510468104.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-14
- Publication Date
- 2026-10-20
AI Technical Summary
[0003]但受限于现有的合成工艺,Na4Fe3(PO4)2P2O7正极材料含有较多马氏体(Maricite)-NaFePO4(Fe/P=1)和Na2FeP2O7(Fe/P=0.5)杂质相,劣化了正极材料的纯度,导致循环性能和倍率性能劣化、实际容量偏低
[0026]本发明提供一种正极活性材料前驱体及其制备方法、正极活性材料、二次电池和用电设备,该正极活性材料前驱体含有少量掺杂金属元素,且其中铁磷比、钠磷比更接近磷酸焦磷酸铁钠的理论化学计量比,降低了合成磷酸焦磷酸铁钠时的元素扩散难度,不仅有利于减少正极活性材料中马氏体(Maricite)-NaFePO4(Fe/P=1)和Na2FeP2O7(Fe/P=0.5)杂质相的生成,提高磷酸焦磷酸铁钠的纯度,还有利于掺杂金属元素在正极活性材料颗粒内部均匀分散,提高掺杂效果的同时更有助于制得高相纯度的掺杂磷酸焦磷酸铁钠材料,从而改善电池的循环性能、倍率性能和充放电比容量。
Smart Images

Figure BDA0005359135590000221 
Figure BDA0005359135590000222 
Figure BDA0005359135590000231
Abstract
Description
Technical Field
[0001] This invention relates to the field of cathode materials for sodium-ion batteries, specifically to a cathode active material precursor and its preparation method, the cathode active material, a secondary battery, and an electrical device. Background Technology
[0002] Na4Fe3(PO4)2P2O7 cathode material has the following advantages: 1) Three-dimensional sodium ion diffusion pathway, which enables rapid insertion / extraction of Na + 2) The volume change is small during cycling, and the cycling stability is good; 3) During charging and discharging, three Na atoms can be reversibly inserted and extracted. + The theoretical specific capacity is 127mAh / g; 4) High voltage platform (approximately 3.1V).
[0003] However, due to limitations in existing synthesis processes, the Na4Fe3(PO4)2P2O7 cathode material contains a large number of martensite-NaFePO4 (Fe / P=1) and Na2FeP2O7 (Fe / P=0.5) impurity phases, which degrades the purity of the cathode material, resulting in poor cycle performance and rate performance, and lower actual capacity. Summary of the Invention
[0004] This invention provides a positive electrode active material precursor and its preparation method, a positive electrode active material, a secondary battery, and an electrical device. The positive electrode active material precursor has high purity, which is beneficial to improving the cycle performance, rate performance, and charge / discharge specific capacity of the battery.
[0005] This invention provides a positive electrode active material precursor, wherein the chemical formula of the positive electrode active material precursor is Na. w Fe x A y P z O m Where 0.60≤(x+y) / z≤0.90, 0<w / z≤1.1, 0<y / x≤0.15, and m satisfies Na w Fe x A y P z O m It is electrically neutral, and A is a metallic element.
[0006] Alternatively, 0.67 ≤ (x + y) / z ≤ 0.75.
[0007] Optionally, 0.1 < w / z ≤ 1.0.
[0008] Optionally, 0 < y / x ≤ 0.04.
[0009] Optionally, 3.5 < m / z ≤ 4.0.
[0010] Optionally, the positive electrode active material precursor is amorphous.
[0011] Optionally, the sum of the mass percentages of Na, Fe, A, and P elements in the positive electrode active material precursor is 45% to 60%.
[0012] Optionally, in the positive electrode active material precursor, element A replaces some of the positions of element Fe in the lattice of the positive electrode active material precursor.
[0013] Optionally, A includes one or more of Cr, Zr, Nb, Cu, V, Ti, and Zn.
[0014] Optionally, the Fe element in the positive electrode active material precursor is in the trivalent state.
[0015] Optionally, the positive electrode active material precursor further includes water of crystallization.
[0016] The present invention also provides a method for preparing the positive electrode active material precursor as described above, comprising: mixing and reacting a first raw material system including an iron source, a first sodium source, an A source, a phosphorus source and an oxidant to prepare the positive electrode active material precursor.
[0017] Optionally, it further includes: adjusting the pH value of the first raw material system, which includes an iron source, a first sodium source, an A source, a phosphorus source and an oxidant, to 2-6, and then reacting the first raw material system to obtain the positive electrode active material precursor.
[0018] Optionally, the process further includes: after the reaction is completed, aging the reaction system for 0.5 to 3 hours, and then washing the product in the reaction system 1 to 6 times to obtain the positive electrode active material precursor.
[0019] Optionally, the iron source includes one or more of ferrous sulfate, ferrous oxalate, iron powder, iron oxide, and ferric nitrate; and / or, the first sodium source includes one or more of sodium dihydrogen phosphate, sodium acetate, sodium pyrophosphate, sodium carbonate, sodium oxalate, and disodium hydrogen phosphate; and / or, the phosphorus source includes one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium pyrophosphate, disodium hydrogen phosphate, and phosphoric acid; and / or, the A source includes one or more of metal oxides, metal salts, and organometallic compounds of Cr, Zr, Nb, Cu, V, Ti, and Zn; and / or, the oxidant includes peroxides, and the peroxides include hydrogen peroxide.
[0020] The present invention also provides a positive electrode active material, which is formed from the positive electrode active material precursor described above or a positive electrode active material precursor prepared according to the preparation method of the positive electrode active material precursor described above.
[0021] Optionally, the lattice structure of the positive electrode active material is a triclinic crystal system with a space group of type P-1; and / or, in the X-ray diffraction pattern, the ratio of the diffraction peak intensity of the positive electrode active material at 33.5°–34° to the diffraction peak intensity at 32.6°–33.4° is 10–18; and / or, the positive electrode active material further includes a carbon coating layer present on at least a portion of the surface of the positive electrode active material.
[0022] The present invention also provides a method for preparing the positive electrode active material as described above, comprising: sintering a second raw material system comprising the positive electrode active material precursor as described above to obtain the positive electrode active material.
[0023] Optionally, the second raw material system further includes a second sodium source, which includes one or more of sodium dihydrogen phosphate, sodium acetate, sodium pyrophosphate, sodium carbonate, sodium oxalate, and disodium hydrogen phosphate; and / or, the second raw material system further includes a carbon source, which includes one or more of glucose, ascorbic acid, oxalic acid, citric acid, fructose, and sucrose; and / or, the sintering temperature is 450–600°C.
[0024] The present invention also provides a secondary battery, including a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive active material layer disposed on the positive current collector, the positive active material layer including the positive active material as described above.
[0025] The present invention also provides an electrical device, including the secondary battery as described above, wherein the secondary battery serves as the power supply for the electrical device.
[0026] This invention provides a precursor for a positive electrode active material and its preparation method, a positive electrode active material, a secondary battery, and an electrical device. The precursor contains a small amount of doped metal elements, and the iron-to-phosphorus ratio and sodium-to-phosphorus ratio are closer to the theoretical stoichiometric ratio of sodium iron pyrophosphate. This reduces the difficulty of element diffusion during the synthesis of sodium iron pyrophosphate, which not only helps to reduce the formation of martensite-NaFePO4 (Fe / P=1) and Na2FeP2O7 (Fe / P=0.5) impurity phases in the positive electrode active material and improves the purity of sodium iron pyrophosphate, but also facilitates the uniform dispersion of doped metal elements within the positive electrode active material particles. This improves the doping effect and helps to obtain high-phase-purity doped sodium iron pyrophosphate material, thereby improving the cycle performance, rate performance, and charge / discharge specific capacity of the battery. Attached Figure Description
[0027] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0028] Figure 1 XRD patterns of the amorphous positive electrode active material precursors of Example 5 and Comparative Examples 1-3;
[0029] Figure 2 XRD patterns of the positive electrode active material precursors of Example 5 and Comparative Examples 1-3;
[0030] Figure 3 Electron micrographs of the amorphous positive electrode active material precursor of Example 5 and the precursors of Comparative Examples 1-3;
[0031] Figure 4 The images shown are electron microscope (EM) images and elemental distribution diagrams of the amorphous cathode active material precursor of Example 5 (the precursor of Example 5 is an EEM image of the amorphous cathode active material precursor of Example 5, Mn is the distribution diagram of Mn element in the amorphous cathode active material precursor of Example 5, Ti is the distribution diagram of Ti element in the amorphous cathode active material precursor of Example 5, Fe is the distribution diagram of Fe element in the amorphous cathode active material precursor of Example 5, P is the distribution diagram of P element in the amorphous cathode active material precursor of Example 5, O is the distribution diagram of O element in the amorphous cathode active material precursor of Example 5, and S is the distribution diagram of S element in the amorphous cathode active material precursor of Example 5).
[0032] Figure 5 Electron micrographs of the positive electrode active materials of Example 5 and Comparative Examples 1-3;
[0033] Figure 6 Charge-discharge curves at 0.1C are shown for batteries prepared using the positive electrode active materials of Example 5 and Comparative Examples 1-3.
[0034] Figure 7 The cycling performance of batteries prepared using the positive electrode active materials of Example 5 and Comparative Examples 1-3 at 1C is shown in the graph.
[0035] Figure 8 The discharge specific capacity test graphs of the batteries prepared using the positive electrode active materials of Example 5 and Comparative Examples 1-3 at 0.1C, 0.2C, 0.5C, 1C, 2C and 5C rates are shown.
[0036] Figure 9 for Figure 2 A magnified XRD pattern of the red area in the image. Detailed Implementation
[0037] To enable those skilled in the art to better understand the present invention, the present invention will be further described in detail below. The specific embodiments listed below are merely descriptions of the principles and features of the present invention, and the examples are only for explaining the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0038] In the existing technology, due to the limitations of the sintering process, the Na4Fe3(PO4)2P2O7 cathode material contains a large number of martensitic (Maricite)-NaFePO4 (Fe / P=1) and Na2FeP2O7 (Fe / P=0.5) impurity phases. Maricite-NaFePO4 lacks sodium ion migration channels, and the Na4Fe3(PO4)2P2O7 cathode material also suffers from poor ion distribution uniformity, resulting in deterioration of cycle performance and rate performance, and lower actual capacity.
[0039] To overcome the shortcomings of the prior art, in a first aspect, embodiments of the present invention provide a positive electrode active material precursor, the chemical formula of which is Na. w Fe x A y P z O m Where 0.60≤(x+y) / z≤0.90, 0<w / z≤1.1, 0<y / x≤0.15, and m satisfies Na w Fe x A y P z O m It is electrically neutral, and A is a metallic element.
[0040] For example, (x+y) / z can be a range consisting of 0.60, 0.70, 0.80, 0.90, or any two of them; w / z can be a range consisting of 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, 1.0, 1.1, or any two of them; y / x can be a range consisting of 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, or any two of them.
[0041] In this invention, the positive electrode active material precursor is a doped sodium iron pyrophosphate (NFPP) precursor.
[0042] m satisfies Naw Fe x A y P z O m It is electrically neutral, i.e., Na w Fe x A y P z O m The sum of the positive and negative charges is 0.
[0043] A represents a metallic element, meaning A is a doped metallic element.
[0044] According to research and analysis, the iron-to-phosphorus ratio and sodium-to-phosphorus ratio of the precursor of this positive electrode active material are closer to the theoretical stoichiometric ratio of sodium iron pyrophosphate, which reduces the difficulty of element diffusion during the synthesis of sodium iron pyrophosphate. This not only helps to reduce the formation of martensite-NaFePO4 (Fe / P=1) and Na2FeP2O7 (Fe / P=0.5) impurity phases in the positive electrode active material and improve the purity of sodium iron pyrophosphate, but also facilitates the uniform dispersion of a small amount of doped metal elements inside the positive electrode active material particles, improving the doping effect and helping to obtain high-phase-purity doped sodium iron pyrophosphate materials, thereby improving the cycle performance, rate performance and charge / discharge specific capacity of the battery.
[0045] In some embodiments of the present invention, 0.67 ≤ (x+y) / z ≤ 0.75. For example, (x+y) / z can be a range of 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, or any combination thereof. By controlling the iron-phosphorus ratio of the present invention to be less than or equal to the theoretical iron-phosphorus ratio of NFPP material (0.75), for the preparation of NFPP, when the iron-phosphorus ratio is slightly lower than its theoretical value of 0.75, the formation of the high iron-phosphorus ratio impurity phase NaFePO4 can be effectively avoided, thereby improving the phase purity of NFPP and resulting in better performance of NFPP preparation compared to high iron-phosphorus ratio precursors.
[0046] In some embodiments of the present invention, 0 < w / z ≤ 1.0. For example, w / z can be a range of 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, or any combination thereof, preferably 0.1 < w / z ≤ 1.0. By controlling the sodium-to-phosphorus ratio of the present invention to satisfy 0 < w / z ≤ 1.0, preferably 0.1 < w / z ≤ 1.0, an appropriate amount of sodium ions is introduced into the precursor of the positive electrode active material, reducing the number of sodium ions migrating during the sintering process of the positive electrode active material. This helps to improve the ion uniformity within the positive electrode active material, increase its high-phase purity, and thus help to improve the cycle performance, rate performance, and charge / discharge specific capacity of the battery.
[0047] In some embodiments of the present invention, 0 < y / x ≤ 0.04. For example, y / x can be a range of 0.01, 0.02, 0.03, 0.04, or any combination thereof. By controlling the ratio of the doped metal element and the iron element within the above range, it is helpful to achieve a more uniform distribution of the doped metal element in the precursor or positive electrode active material, which can balance a good doping effect and the stability of the crystal structure of the positive electrode active material, thereby helping to improve the cycle performance, rate performance, and charge / discharge specific capacity of the battery.
[0048] In some embodiments of the present invention, 3.5 < m / z ≤ 4.0. For example, m / z can be a range of 3.6, 3.7, 3.8, 3.9, 4.0, or any combination thereof. A phosphorus-to-oxygen ratio m / z satisfying the above range indicates that the presence of phosphorus in the cathode active material precursor includes phosphate and / or pyrophosphate, which helps to generate a high-purity sodium iron pyrophosphate-based cathode material and improves the battery's cycle performance, rate performance, and charge / discharge specific capacity.
[0049] In some embodiments of the present invention, the positive electrode active material precursor is amorphous.
[0050] The positive electrode active material precursor of this invention is amorphous, i.e., an amorphous precursor. This can be verified by XRD testing, which shows no obvious characteristic diffraction peaks, indicating an amorphous structure.
[0051] The cathode active material precursor of this invention is amorphous. Its XRD pattern shows no obvious diffraction peaks. This amorphous precursor lacks a distinct crystal structure and has a relatively uniform elemental distribution, which facilitates ion diffusion within it. This, in turn, helps improve the ion uniformity of the cathode active material, promoting the formation of a purer crystalline phase during subsequent processing and reducing the formation of impurity phases. This, in turn, improves the purity of the cathode material, thereby enhancing the battery's cycle performance, rate performance, and charge / discharge specific capacity.
[0052] In some embodiments of the present invention, the sum of the mass percentages of Na, Fe, A, and P elements in the positive electrode active material precursor is 45% to 60%.
[0053] The sum of the mass percentages of Na, Fe, A, and P elements in the precursor of the positive electrode active material is calculated according to the following formula: Sum of the mass percentages of Na, Fe, A, and P elements in the precursor of the positive electrode active material = (molar amount of Na, Fe, A, and P × relative atomic mass) / (relative molecular mass of the precursor) × 100%.
[0054] In some embodiments of the present invention, element A in the positive electrode active material precursor replaces some of the positions of element Fe in the lattice of the positive electrode active material precursor.
[0055] These doped metal elements can replace some of the iron elements embedded in the crystal framework of the cathode active material, reducing the amount of iron elements diffused during the sintering process of the cathode active material. This helps to improve the diffusion effect of iron and phosphorus during the preparation of the cathode active material, improve the ionic uniformity of the cathode active material, avoid the formation of martensite-NaFePO4 (Fe / P=1) and Na2FeP2O7 (Fe / P=0.5) impurity phases, improve the phase purity of the cathode active material, and thus improve the cycle performance, rate performance and charge / discharge specific capacity of the battery.
[0056] Specifically, A may include one or more of Ni, Co, Mn, Cr, Zr, Nb, Cu, V, Ti, Zn, Al, Ga, and Mg.
[0057] Preferably, A may include one or more of Cr, Zr, Nb, Cu, V, Ti, and Zn. These doped metal elements exhibit better uniformity in the cathode active material precursor and help improve the diffusion effect of iron and phosphorus during the preparation of the cathode active material. This also helps improve the ionic uniformity of the cathode active material, avoids the formation of martensitic NaFePO4 (Fe / P=1) and Na2FeP2O7 (Fe / P=0.5) impurity phases, improves the phase purity of the cathode active material, and further enhances the battery's cycle performance, rate performance, and charge / discharge specific capacity.
[0058] Metal ion doping helps improve intrinsic electronic conductivity and sodium ion diffusion rate, thereby increasing the electronic conductivity of the cathode active material. More importantly, these doped metal elements can replace some iron elements embedded in the crystal framework of the cathode active material, and these doped metal elements can be uniformly distributed in the cathode active material precursor, improving the diffusion effect of iron and phosphorus during the preparation of the cathode active material, helping to improve the ionic uniformity of the cathode active material, which is beneficial to obtaining cathode active materials with good chemical performance uniformity. This, in turn, helps to improve the electrochemical performance of the battery, such as cycle performance and rate performance. It can also avoid the formation of martensitic (Maricite)-NaFePO4 (Fe / P=1) and Na2FeP2O7 (Fe / P=0.5) impurity phases. In the cathode active material precursor of the embodiments of the present invention, the doped metal elements are uniformly distributed, which helps to improve the ionic uniformity of the cathode active material, avoid the formation of impurity phases, help improve cycle performance, rate performance, and increase charge and discharge specific capacity.
[0059] In some embodiments of the present invention, the Fe element in the positive electrode active material precursor is in the trivalent state. This helps to improve cycle life, rate capability, and other performance characteristics, and increases the charge / discharge specific capacity.
[0060] In some embodiments of the present invention, the positive electrode active material precursor further includes water of crystallization.
[0061] The positive electrode active material precursor of the present invention also contains water of crystallization, that is, the chemical composition can be Na. w Fe x A y P z O m ·aH2O, when a equals 0, the precursor does not contain water of crystallization; when a is greater than 0, the precursor contains water of crystallization, and a / z satisfies 0≤a / z≤2.5. For example, a / z can be a range of 0, 0.5, 1, 1.5, 2, 2.5 or any two of them.
[0062] The precursor of the positive electrode active material of the present invention also contains water of crystallization. The presence of water of crystallization can provide a certain lubrication effect between material particles, improve the dispersibility of the material, and facilitate more uniform mixing in the subsequent synthesis process of the positive electrode active material, thereby improving the uniformity and consistency of the material.
[0063] Secondly, embodiments of the present invention provide a method for preparing the above-mentioned positive electrode active material precursor, comprising: mixing and reacting a first raw material system including an iron source, a first sodium source, an A source, a phosphorus source and an oxidant to prepare the positive electrode active material precursor.
[0064] Conventional iron, sodium, a, and phosphorus sources in this field can all be used to prepare precursors for positive electrode active materials.
[0065] The role of the aforementioned oxidant is to ensure that iron ions are oxidized, thereby reducing the oxidation state of iron to trivalent, thus improving the electrochemical performance of the positive electrode active material.
[0066] The above reaction causes iron, sodium, phosphorus, and dopant elements to combine and form a precursor for the positive electrode active material.
[0067] The preparation method of the above-mentioned positive electrode active material precursor is simple to operate.
[0068] In practice, the iron source, the first sodium source, the A source, the phosphorus source and the oxidant can be added to water (such as deionized water) and stirred to obtain their respective mixed solutions. These mixed solutions can then be used to prepare the above-mentioned positive electrode active material precursor.
[0069] Furthermore, a mixed solution comprising an iron source, a first sodium source, and an A source can be obtained by first mixing, and then a solution comprising a phosphorus source and a solution comprising an oxidant can be simultaneously added dropwise to the mixed solution to obtain the first raw material system.
[0070] It is understandable that the amount of iron source, first sodium source, A source, phosphorus source, and other raw materials added in the first raw material system can be adjusted according to the chemical composition of the positive electrode active material precursor, thereby ensuring that the expected positive electrode active material precursor is obtained.
[0071] In some embodiments of the present invention, the preparation method of the above-mentioned positive electrode active material precursor further includes: adjusting the pH value of a first raw material system comprising an iron source, a first sodium source, an A source, a phosphorus source and an oxidant to 2 to 6, and then reacting the first raw material system to obtain the positive electrode active material precursor.
[0072] For example, the pH value of the first raw material system can be a range of 2.0, 3.0, 4.0, 5.0, 6.0 or any two of them.
[0073] Adjusting the pH value of the first raw material system helps to form an amorphous form of the positive electrode active material precursor, thereby preparing an amorphous precursor.
[0074] In the specific implementation process, the pH value of the raw material system can be adjusted by the following process: adding an alkaline solution (such as sodium hydroxide aqueous solution and / or ammonia water) dropwise to the first raw material system to adjust the pH value of the first raw material system to 2 to 6.
[0075] It is understandable that sodium hydroxide used to adjust the pH value can serve as the first sodium source to provide sodium ions for the precursor of the amorphous positive electrode active material. In this case, the sodium hydroxide mentioned above is the first sodium source, and no other sodium source needs to be added.
[0076] In some embodiments of the present invention, the above preparation method may further include: after the reaction is completed, aging the reaction system for 0.5 to 3 hours, for example, 0.5, 1, 2, 3 hours or any combination thereof, and then washing the product in the reaction system 1 to 6 times, for example, 1, 2, 3, 4, 5, 6 times or any combination thereof, to obtain the positive electrode active material precursor.
[0077] The above washing can be done by washing with water.
[0078] Understandably, after washing, the product can be dried at 80–120°C (e.g., oven drying) and then sintered at 300–400°C to obtain the precursor of the positive electrode active material.
[0079] In some embodiments of the present invention, the iron source includes one or more of ferrous sulfate, ferrous oxalate, iron powder, iron oxide, and ferric nitrate.
[0080] In some embodiments, the first sodium source includes one or more of sodium dihydrogen phosphate, sodium acetate, sodium pyrophosphate, sodium carbonate, sodium oxalate, and disodium hydrogen phosphate.
[0081] In some embodiments, the phosphorus source includes one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium pyrophosphate, disodium hydrogen phosphate, and phosphoric acid.
[0082] In some embodiments, source A includes one or more of the following: metal oxides, metal salts, and organometallic compounds of Ni, Co, Mn, Cr, Zr, Nb, Cu, V, Ti, Zn, Al, Ga, and Mg. For example, source A may include one or more of the following: nickel oxide, cobalt oxide, manganese sulfate, magnesium sulfate, titanium sulfate, chromium oxide, zirconium oxide, niobium oxide, copper oxide, vanadium phosphate, zinc sulfide, aluminum oxide, and gallium oxide.
[0083] Preferably, the A source may include one or more of the following: metal oxides, metal salts, and organometallic compounds of Cr, Zr, Nb, Cu, V, Ti, and Zn. The aforementioned A source (doping source) can uniformly dope metal elements into the cathode active material precursor, which helps improve the ionic uniformity of the cathode active material, avoids the formation of impurity phases, helps improve cycle life, rate capability, and other performance characteristics, and increases the charge / discharge specific capacity.
[0084] In some embodiments, the oxidant includes a peroxide, which may include hydrogen peroxide. The peroxide can oxidize ferrous ions.
[0085] In the above preparation method system, under the premise of sufficient raw materials, the element content of the amorphous positive electrode active material precursor can be controlled by synergistically regulating pH and aging time. Washing helps to remove impurities, so that the chemical formula and structure of the positive electrode active material precursor meet expectations.
[0086] Thirdly, embodiments of the present invention also provide a positive electrode active material, which is formed from the above-mentioned positive electrode active material precursor or a positive electrode active material precursor prepared according to the above-mentioned method for preparing the positive electrode active material precursor.
[0087] Based on this positive electrode active material precursor, the positive electrode active material has excellent rate performance, cycle performance and charge / discharge specific capacity, which will not be elaborated here.
[0088] In some embodiments, the crystal lattice structure of the above-mentioned positive electrode active material is a triclinic crystal system with a space group of type P-1.
[0089] In some embodiments, in the X-ray diffraction pattern, the ratio of the diffraction peak intensity at 33.5°–34° to the diffraction peak intensity at 32.6°–33.4° of the positive electrode active material is 10–18. The diffraction peak intensity at 33.5°–34° represents the peak intensity of the main phase of the positive electrode active material (such as the sodium iron pyrophosphate-based phase), and the diffraction peak intensity at 32.6°–33.4° represents the impurity peak intensity of NaFePO4. The relatively large ratio of the above two peak intensities indicates that the positive electrode active material has a low impurity phase content and high purity.
[0090] In some embodiments, the positive electrode active material further includes a carbon coating layer present on at least a portion of the surface of the positive electrode active material. That is, the positive electrode active material may also have a core-shell structure, comprising a core and a carbon coating layer present on at least a portion of the surface of the core. The synergistic effect of the uniformly dispersed doped metal ions and the carbon coating layer in the core-shell structured positive electrode active material can further improve electronic conductivity and ion conduction efficiency, thereby improving the cycle and rate performance of the battery.
[0091] The following uses the chemical composition of the core of the above positive electrode active material as Na4Fe x A y (PO4)2P2O7 (0<y / x≤0.1, 0.60≤(x+y) / 4≤0.90) is used as an example for the positive electrode active material (the chemical formula can be represented as Na4Fe). x A y The properties of (PO4)2P2O7@C will be explained in detail.
[0092] The low electronic conductivity of the Na4Fe3(PO4)2P2O7 cathode active material limits its ability to co-transport electrons and ions at high current densities. Electronic conductivity depends on electron transfer within the conductive medium and intrinsic electronic conductivity. While existing research has explored carbon coating, particle nano-sizing, and metal ion doping to improve electronic conductivity, limitations remain. For example, carbon coating effectively enhances electron transfer within the conductive medium, but its improvement on intrinsic electronic conductivity is not significant. Particle nano-sizing primarily improves cycle and rate performance by shortening the transport paths of ions and electrons. In this invention, the synergistic effect of uniformly dispersed doped metal ions and the carbon coating layer in the core-shell structured cathode active material further enhances electronic conductivity and ion conduction efficiency, thereby improving the battery's cycle and rate performance.
[0093] Currently, the main preparation method for Na4Fe3(PO4)2P2O7@C material is the solid-state reaction method. Specifically, Na4Fe3(PO4)2P2O7@C material is synthesized by solid-state reaction (solid-state ball milling and sand milling, etc.) using FePO4, phosphorus source, sodium source, A source and carbon source raw materials. However, the above preparation method has some problems, including: 1) When using FePO4 as raw material, ball milling and sand milling can only achieve micron or submicron level mixing between raw material particles (FePO4 Fe / P≈1, while Na4Fe3(PO4)2P2O7 Fe / P≈0.75), and the requirement for some ions to diffuse into / out of FePO4 particles is difficult to meet; 2) The sintering temperature of Na4Fe3(PO4)2P2O7@C is relatively low (about 500-600℃), which is not conducive to ion diffusion in the precursor. The above-mentioned problems can easily lead to the presence of more martensitic (Maricite)-NaFePO4 (Fe / P=1) and Na2FeP2O7 (Fe / P=0.5) impurity phases in the synthesized Na4Fe3(PO4)2P2O7@C material. Maricite-NaFePO4 lacks sodium ion migration channels, resulting in a lower actual capacity. While using ferric hydrogen phosphate (Fe / P≈0.75) as a raw material can solve the problem of Fe and P ion diffusion, the synthesis method of Na4Fe3(PO4)2P2O7 using ferric hydrogen phosphate as a raw material is mainly a solid-state reaction method (solid-state ball milling and sand milling, etc.). Specifically, ferric hydrogen phosphate, sodium source, A source and carbon source are ground and dried to form a macroscopically homogeneous mixture, and then calcined to form Na4Fe3(PO4)2P2O7 crystals. In the above calcination process (such as high-temperature calcination), doped atoms and all sodium ions need to migrate to form Na4Fe3(PO4)2P2O7 crystals. However, the low calcination temperature will lead to the formation of impurity phases, which will degrade the cycle performance, rate performance and capacity of the positive electrode active material.
[0094] Based on this, in a fourth aspect, the present invention also provides a method for preparing the above-mentioned positive electrode active material, comprising: sintering a second raw material system including the above-mentioned positive electrode active material precursor to obtain the positive electrode active material.
[0095] The aforementioned cathode active material precursor has high purity and few impurities. It also includes doped metal elements, which avoids doping during the sintering (calcination) process and facilitates the migration of sodium elements during sintering. In addition, the aforementioned cathode active material precursor may also include some sodium ions, which reduces the number of sodium ions migrating during sintering. Sodium ions are more easily and uniformly dispersed, which helps to improve the ion uniformity of the cathode active material obtained by solid-phase reaction, reduce impurities in the cathode active material, and thus obtain a cathode active material with better cycle performance, rate performance, and capacity.
[0096] Understandably, the above sintering process should be carried out in an inert atmosphere.
[0097] The preparation method is simple to operate.
[0098] In specific implementation, the second raw material system including the above-mentioned positive electrode active material precursor can be mixed with water (such as deionized water) and then ground (such as ball milling in a high-speed ball mill) to obtain a precursor solution; then the precursor solution is dried (such as spray drying) to obtain precursor powder, and then the precursor powder is sintered in an inert atmosphere (such as flowing argon) to obtain the above-mentioned positive electrode active material.
[0099] In the above sintering process, the precursor powder can be placed in a container (e.g., a ceramic boat) and then placed in a sintering device (e.g., a tube furnace). Sintering is then carried out in an inert atmosphere, and the positive electrode active material of the present invention is obtained by grinding.
[0100] In some embodiments of the present invention, the second raw material system further includes a second sodium source.
[0101] In some embodiments, the second sodium source includes one or more of sodium dihydrogen phosphate, sodium acetate, sodium pyrophosphate, sodium carbonate, sodium oxalate, and disodium hydrogen phosphate.
[0102] In some embodiments, the second raw material system further includes a carbon source, which helps to form a carbon coating layer on at least a portion of the surface of the positive electrode active material.
[0103] Specifically, the carbon source mentioned above may include glucose (C6H4O3). 12 O6), ascorbic acid, oxalic acid, citric acid, fructose, sucrose, or one or more of these.
[0104] In addition, the aforementioned second raw material system may also include phosphorus sources and iron sources, such as iron phosphate (FePO4) and NH4H2PO4.
[0105] In some embodiments, the sintering temperature is 450–600°C, for example, a range of 450, 500, 550, 600°C or any combination thereof. Lower sintering temperatures help reduce energy consumption, meaning that the present invention can prepare cathode active materials with better cycle performance, rate performance, and higher capacity with lower energy consumption.
[0106] Fifthly, embodiments of the present invention also provide a secondary battery, including a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive active material layer disposed on the positive current collector, the positive active material layer including the aforementioned positive active material.
[0107] Based on this positive electrode active material or its precursor, the secondary battery exhibits excellent rate performance, cycle performance, and capacity, which will not be elaborated further here.
[0108] In the specific preparation of the positive electrode sheet, for example, the positive active material of the present invention can be dispersed with a conductive agent and a binder in an appropriate amount of N-methylpyrrolidone (NMP) solvent, and thoroughly stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is uniformly coated on the positive current collector, and after drying, rolling and slitting, the positive electrode sheet is obtained. In one specific embodiment, the positive active layer comprises, by mass percentage, 70-99 wt% of positive active material, 0.5-15 wt% of conductive agent, and 0.5-15 wt% of binder, and more specifically, 80-98 wt% of positive active material, 1-10 wt% of conductive agent, and 1-10 wt% of binder.
[0109] The positive electrode current collector can be made of at least one of aluminum foil or nickel foil; the conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, carbon fiber, carbon nanotubes, and conductive graphite; the binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, and polyurethane.
[0110] As can be imagined, the secondary battery of this invention, in addition to the above-mentioned positive electrode, also includes a negative electrode, an electrolyte, and a separator.
[0111] The embodiments of the present invention are not strictly limited to the negative electrode active material in the negative electrode sheet. It can be the negative electrode active material commonly used in sodium-ion batteries, such as at least one of hard carbon, soft carbon, titanium-based materials, metal oxides and sulfides.
[0112] The embodiments of the present invention do not strictly limit the selection of electrolyte, and may include one or more of the solvents commonly used in sodium-ion battery electrolytes, as well as the electrolyte sodium salts commonly used in sodium-ion electrolytes. For example, the solvent may be ethylene carbonate, propylene carbonate, butene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, methyl ethyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, γ-butyrolactone, etc.; the electrolyte may be one or more of sodium hexafluorophosphate, sodium bis(trifluoromethanesulfonyl)imide, sodium bis(fluorosulfonyl)imide, and sodium fluorotrifluoromethanesulfonylimide.
[0113] The embodiments of the present invention do not strictly limit the choice of membrane material. It can be one of the membrane materials commonly used in sodium-ion batteries, such as polypropylene membrane (PP), polyethylene membrane (PE), polypropylene / polyethylene double-layer composite membrane (PP / PE), polyimide electrospun membrane (PI), polypropylene / polyethylene / polypropylene triple-layer composite membrane (PP / PE / PP), cellulose nonwoven membrane, and membrane with ceramic coating.
[0114] In the preparation of secondary batteries (sodium-ion batteries), the positive electrode, separator, and negative electrode are wound or stacked to obtain a bare cell, which is then packaged into a pre-stamped aluminum-plastic film bag or aluminum shell. After the packaged battery is dried, the electrolyte is injected into the dried battery. The battery is then left to stand, formed, and resealed to complete the preparation of the secondary battery.
[0115] Sixthly, embodiments of the present invention also provide an electrical device, including the aforementioned secondary battery, wherein the secondary battery serves as the power supply for the electrical device.
[0116] The present invention will be further described below through specific embodiments and comparative examples. Unless otherwise specified, the reagents, materials and instruments used below are all conventional reagents, materials and instruments, all of which are commercially available, and the reagents and materials involved can also be synthesized by conventional synthetic methods.
[0117] Example 1
[0118] This embodiment provides a method for preparing a positive electrode active material precursor, including:
[0119] MnSO4 and FeSO4·7H2O, NH4H2PO4, and H2O2, respectively, with a raw material molar ratio of 0.02:3:4.8:1, were added to deionized water and stirred until colorless and transparent to obtain manganese sulfate aqueous solution, ferrous sulfate aqueous solution, ammonium dihydrogen phosphate aqueous solution, and hydrogen peroxide aqueous solution. Ammonium dihydrogen phosphate aqueous solution and hydrogen peroxide aqueous solution were simultaneously added dropwise to a mixed solution of manganese sulfate aqueous solution and ferrous sulfate aqueous solution to obtain the reaction system.
[0120] A sodium hydroxide aqueous solution was added dropwise to the reaction system to adjust the pH of the reaction system to 6, allowing the reaction to occur. After aging for 1.5 hours, the reaction product was filtered under pressure, washed with water four times, and then dried and sintered to obtain the precursor of the positive electrode active material. The molar ratio of sodium, manganese, iron, and phosphorus in the precursor was found to be 1.85:0.02:2.96:4.
[0121] This embodiment also provides a method for preparing a positive electrode active material, including:
[0122] The amorphous positive electrode active material precursor, sodium acetate, and glucose of this embodiment were added to deionized water to obtain a second raw material system. This second raw material system was then ball-milled in a high-speed ball mill to obtain a precursor solution. The precursor solution was then spray-dried and sintered at 500°C under flowing argon gas to obtain the positive electrode active material Na4Mn. 0.02 Fe 2.96 (PO4)2P2O7@C.
[0123] Example 2
[0124] This embodiment is basically the same as Embodiment 1, except that:
[0125] In the preparation of the positive electrode active material precursor, MgSO4 is used to replace MnSO4, and the molar ratio of sodium, magnesium, iron and phosphorus in the positive electrode active material precursor is 1.85:0.04:2.94:4.
[0126] The chemical formula of the positive electrode active material in Example 2 is Na4Mg. 0.04 Fe 2.94 (PO4)2P2O7@C.
[0127] All other conditions remain unchanged.
[0128] Example 3
[0129] This embodiment is basically the same as Embodiment 1, except that:
[0130] In the preparation of the positive electrode active material precursor, Ti(SO4)2 is used to replace MnSO4, and the molar ratio of sodium, titanium, iron and phosphorus in the positive electrode active material precursor is 1.85:0.03:2.95:4.
[0131] The chemical formula of the positive electrode active material in Example 3 is Na4Ti 0.03 Fe 2.95 (PO4)2P2O7@C;
[0132] All other conditions remain unchanged.
[0133] Example 4
[0134] This embodiment is basically the same as Embodiment 1, except that:
[0135] In the preparation of the positive electrode active material precursor, MgSO4 and MnSO4 are used to replace MnSO4, and the molar ratio of sodium, manganese, magnesium, iron and phosphorus in the positive electrode active material precursor is 1.85:0.02:0.02:2.94:4.
[0136] The chemical formula of the positive electrode active material in Example 4 is Na4Mn. 0.02 Mg0.02 Fe 2.94 (PO4)2P2O7@C;
[0137] All other conditions remain unchanged.
[0138] Example 5
[0139] This embodiment is basically the same as Embodiment 1, except that:
[0140] In the preparation of the positive electrode active material precursor, Ti(SO4)2 and MnSO4 are used to replace MnSO4, and the molar ratio of sodium, manganese, titanium, iron and phosphorus in the positive electrode active material precursor is 1.85:0.02:0.02:2.94:4.
[0141] The positive electrode active material in Example 5 has the chemical formula Na4Mn. 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C;
[0142] All other conditions remain unchanged.
[0143] Example 6
[0144] This embodiment is basically the same as Embodiment 1, except that:
[0145] In the preparation of the positive electrode active material precursor, MgSO4 is used to replace MnSO4, and the molar ratio of sodium, magnesium, iron and phosphorus in the positive electrode active material precursor is 1.85:0.3:2.68:4.
[0146] The chemical formula of the positive electrode active material in Example 6 is Na₄Mg. 0.3 Fe 2.68 (PO4)2P2O7@C.
[0147] All other conditions remain unchanged.
[0148] Example 7
[0149] This embodiment is basically the same as Embodiment 1, except that:
[0150] In the preparation of the positive electrode active material precursor, the pH of the reaction system was adjusted to 1.5 to allow the reaction to occur. After aging for 0.5 h, the reaction product was filtered under pressure and washed with water 6 times. MnSO4 was replaced with Ti(SO4)2 and MnSO4, and the molar ratio of sodium, manganese, titanium, iron and phosphorus in the positive electrode active material precursor was 0.33:0.02:0.02:2.94:3.31.
[0151] In the preparation process of the positive electrode active material, NH4H2PO4 is added to the second raw material system, and the chemical formula of the positive electrode active material is Na4Mn. 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C;
[0152] All other conditions remain unchanged.
[0153] Example 8
[0154] This embodiment is basically the same as Embodiment 1, except that:
[0155] In the preparation of the positive electrode active material precursor, the pH of the reaction system was adjusted to 8 to allow the reaction to occur. After aging for 3 hours, the reaction product was filtered by pressure and washed once with water. MnSO4 was replaced with Ti(SO4)2 and MnSO4, and the molar ratio of sodium, manganese, titanium, iron and phosphorus in the positive electrode active material precursor was 3.63:0.02:0.02:2.94:4.
[0156] The chemical formula of the positive electrode active material is Na4Mn 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C;
[0157] All other conditions remain unchanged.
[0158] Example 9
[0159] This embodiment is basically the same as Embodiment 1, except that:
[0160] In the preparation of the positive electrode active material precursor, Ti(SO4)2 and MnSO4 are used to replace MnSO4, and the molar ratio of sodium, manganese, titanium, iron and phosphorus in the positive electrode active material precursor is 1.2:0.02:0.02:2.94:4.97.
[0161] In the preparation process of the positive electrode active material, FePO4 is added to the second raw material system, and the chemical formula of the positive electrode active material is Na4Mn. 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C;
[0162] All other conditions remain unchanged.
[0163] Example 10
[0164] This embodiment is basically the same as Embodiment 1, except that: in the preparation process of the positive electrode active material precursor, Ti(SO4)2 and MnSO4 are used to replace MnSO4, and the molar ratio of sodium, manganese, titanium, iron and phosphorus in the positive electrode active material precursor is 1.25:0.02:0.02:2.64:4;
[0165] In the preparation process of the positive electrode active material, FePO4 is added to the second raw material system, and the chemical formula of the positive electrode active material is Na4Mn. 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C.
[0166] Example 11
[0167] This embodiment is basically the same as Embodiment 1, except that: in the preparation process of the positive electrode active material precursor, Ti(SO4)2 and MnSO4 are used to replace MnSO4, and the molar ratio of sodium, manganese, titanium, iron and phosphorus in the positive electrode active material precursor is 1.76:0.02:0.02:2.76:4.
[0168] In the preparation process of the positive electrode active material, FePO4 is added to the second raw material system, and the chemical formula of the positive electrode active material is Na4Mn. 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C.
[0169] Example 12
[0170] This embodiment is basically the same as Embodiment 1, except that: in the preparation process of the positive electrode active material precursor, Ti(SO4)2 and MnSO4 are used to replace MnSO4, and the molar ratio of sodium, manganese, titanium, iron and phosphorus in the positive electrode active material precursor is 4.32:0.02:0.02:2.60:4;
[0171] In the preparation process of the positive electrode active material, FePO4 is added to the second raw material system, and the chemical formula of the positive electrode active material is Na4Mn. 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C.
[0172] Example 13
[0173] This embodiment is basically the same as Embodiment 1, except that: in the preparation process of the positive electrode active material precursor, Ti(SO4)2 and MnSO4 are used to replace MnSO4, and the molar ratio of sodium, manganese, titanium, iron and phosphorus in the positive electrode active material precursor is 1.85:0.06:0.05:2.87:4.
[0174] The chemical formula of the positive electrode active material is Na4Mn 0.06 Ti 0.05 Fe 2.87 (PO4)2P2O7@C.
[0175] Example 14
[0176] This embodiment is basically the same as Embodiment 1, except that: in the preparation process of the positive electrode active material precursor, Ti(SO4)2 and MnSO4 are used to replace MnSO4, and the molar ratio of sodium, manganese, titanium, iron and phosphorus in the positive electrode active material precursor is 3.63:0.02:0.02:2.83:4;
[0177] In the preparation process of the positive electrode active material, FePO4 is added to the second raw material system, and the chemical formula of the positive electrode active material is Na4Mn. 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C.
[0178] Example 15
[0179] This embodiment is basically the same as Embodiment 1, except that: in the preparation process of the positive electrode active material precursor, Ti(SO4)2 and MnSO4 are used to replace MnSO4, and the molar ratio of sodium, manganese, titanium, iron and phosphorus in the positive electrode active material precursor is 4.32:0.02:0.02:2.4:4.
[0180] In the preparation process of the positive electrode active material, FePO4 is added to the second raw material system, and the chemical formula of the positive electrode active material is Na4Mn. 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C.
[0181] Example 16
[0182] This embodiment is basically the same as Embodiment 5, except that: the preparation method of the positive electrode active material is as follows: the precursor solution is spray-dried and then sintered at 400°C in flowing argon gas to obtain the positive electrode active material Na4Mn. 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C.
[0183] Example 17
[0184] This embodiment is basically the same as Embodiment 5, except that: the preparation method of the positive electrode active material is as follows: the precursor solution is spray-dried and then sintered at 650°C in flowing argon gas to obtain the positive electrode active material Na4Mn. 0.02 Ti 0.02Fe 2.94 (PO4)2P2O7@C.
[0185] Example 18
[0186] This embodiment is basically the same as Embodiment 1, except that:
[0187] In the preparation of the positive electrode active material precursor, Cr2(SO4)3 is used to replace MnSO4, and the molar ratio of sodium, chromium, iron and phosphorus in the positive electrode active material precursor is 1.85:0.02:2.96:4.
[0188] The positive electrode active material in Example 18 has the chemical formula Na₄Cr₂ 0.02 Fe 2.96 (PO4)2P2O7@C.
[0189] All other conditions remain unchanged.
[0190] Example 19
[0191] This embodiment is basically the same as Embodiment 1, except that:
[0192] In the preparation of the positive electrode active material precursor, ZrCl4 is used to replace MnSO4, and the molar ratio of sodium, zirconium, iron and phosphorus in the positive electrode active material precursor is 1.85:0.02:2.96:4.
[0193] The positive electrode active material in Example 19 has the chemical formula Na4Zr. 0.02 Fe 2.96 (PO4)2P2O7@C.
[0194] All other conditions remain unchanged.
[0195] Example 20
[0196] This embodiment is basically the same as Embodiment 1, except that:
[0197] In the preparation of the positive electrode active material precursor, NbCl4 is used to replace MnSO4, and the molar ratio of sodium, niobium, iron and phosphorus in the positive electrode active material precursor is 1.85:0.02:2.96:4.
[0198] The positive electrode active material of Example 20 has the chemical formula Na4Nb. 0.02 Fe 2.96 (PO4)2P2O7@C.
[0199] All other conditions remain unchanged.
[0200] Example 21
[0201] This embodiment is basically the same as Embodiment 1, except that:
[0202] In the preparation of the positive electrode active material precursor, CuSO4 is used to replace MnSO4, and the molar ratio of sodium, copper, iron and phosphorus in the positive electrode active material precursor is 1.85:0.02:2.96:4.
[0203] The positive electrode active material in Example 21 has the chemical formula Na₄Cu. 0.02 Fe 2.96 (PO4)2P2O7@C.
[0204] All other conditions remain unchanged.
[0205] Example 22
[0206] This embodiment is basically the same as Embodiment 1, except that:
[0207] In the preparation of the positive electrode active material precursor, VOSO4 is used to replace MnSO4, and the molar ratio of sodium, vanadium, iron and phosphorus in the positive electrode active material precursor is 1.85:0.02:2.96:4.
[0208] The positive electrode active material in Example 22 has the chemical formula Na4V. 0.02 Fe 2.96 (PO4)2P2O7@C.
[0209] All other conditions remain unchanged.
[0210] Example 23
[0211] This embodiment is basically the same as Embodiment 1, except that:
[0212] In the preparation of the positive electrode active material precursor, ZnSO4 is used to replace MnSO4, and the molar ratio of sodium, zinc, iron and phosphorus in the positive electrode active material precursor is 1.85:0.02:2.96:4.
[0213] The positive electrode active material in Example 22 has the chemical formula Na4Zn. 0.02 Fe 2.96 (PO4)2P2O7@C.
[0214] All other conditions remain unchanged.
[0215] Comparative Example 1
[0216] This comparative example provides a method for preparing an undoped positive electrode active material precursor, including:
[0217] FeSO4·7H2O, NH4H2PO4, and H2O2 were added to deionized water and stirred until colorless and transparent to obtain ferrous sulfate aqueous solution, ammonium dihydrogen phosphate aqueous solution, and hydrogen peroxide aqueous solution. Ammonium dihydrogen phosphate aqueous solution and hydrogen peroxide aqueous solution were simultaneously added dropwise to a mixed solution of manganese sulfate aqueous solution and ferrous sulfate aqueous solution to obtain the reaction system.
[0218] A sodium hydroxide aqueous solution was added dropwise to the reaction system to adjust the pH of the reaction system to 6, allowing the reaction to occur. After aging for 1.5 hours, the reaction product was filtered under pressure, washed with water four times, dried, and sintered to obtain an undoped positive electrode active material precursor. The molar ratio of sodium, iron, and phosphorus in the undoped positive electrode active material precursor was 1.85:2.94:4.
[0219] This comparative example also provides a method for preparing a positive electrode active material, including:
[0220] Undoped positive electrode active material precursor, sodium acetate, manganese sulfate, titanium sulfate Ti(SO4)2, and glucose of this comparative example were added to deionized water to obtain a raw material system. The raw material system was then ball-milled in a high-speed ball mill to obtain a precursor solution.
[0221] The precursor solution was then spray-dried and sintered in flowing argon gas to obtain the positive electrode active material Na4Mn. 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C.
[0222] Comparative Example 2
[0223] The Fe3(HPO4)4 precursor was prepared according to Example 1 of patent document CN116924369A, specifically including the following steps:
[0224] 1. First, add 50.0 kg of ferrous sulfate solution to a 100 L reactor. The ferrous sulfate solution has an iron content of 6.0%. Then, simultaneously add hydrogen peroxide solution and ammonium dihydrogen phosphate solution. The molar ratio of n(H2O2):n(FeSO4) is 0.5, and the molar ratio of n(NH4H2PO4):n(Fe) is 1.5. Adjust the mass fraction of ammonium dihydrogen phosphate solution to 20%, the dropping rate of hydrogen peroxide solution to 60 mL / min, and the dropping rate of ammonium dihydrogen phosphate solution to 120 mL / min. Carry out the oxidation reaction at room temperature for 1 h.
[0225] 2. Add ammonia to adjust the pH to 1.8, and carry out the aging reaction at room temperature for 1 hour. After the reaction is completed, filter the filter cake by pressure, and wash it three times with four times the amount of water to obtain low-sulfur and low-impurity battery-grade ferric hydrogen phosphate.
[0226] 3. The battery-grade ferric hydrogen phosphate is flash-dried, then sintered at 400℃ for 2 hours, and then pulverized to obtain battery-grade anhydrous ferric hydrogen phosphate.
[0227] This comparative example also provides a method for preparing a positive electrode active material, including:
[0228] The above Fe3(HPO4)4 precursor, sodium acetate, manganese sulfate, titanium sulfate Ti(SO4)2, and glucose were added to deionized water to obtain a raw material system. The raw material system was then ball-milled in a high-speed ball mill to obtain a precursor solution.
[0229] The precursor solution was then spray-dried and sintered in flowing argon gas to obtain the positive electrode active material Na4Mn. 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C.
[0230] Comparative Example 3
[0231] The FePO4·2H2O precursor was purchased from Hunan Yacheng New Energy Co., Ltd.
[0232] This comparative example also provides a method for preparing a positive electrode active material, including:
[0233] The above FePO4·2H2O precursor, sodium acetate, manganese sulfate, titanium sulfate Ti(SO4)2, and glucose were added to deionized water to obtain a raw material system. Then, the raw material system was ball-milled in a high-speed ball mill to obtain a precursor solution.
[0234] The precursor solution was then spray-dried and sintered in flowing argon gas to obtain the positive electrode active material Na4Mn. 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C.
[0235] Comparative Example 4
[0236] Na was prepared according to Example 1 of patent document CN118479443A. 0.64 Fe 0.72 H 0.2 PO4 precursor, including the following steps:
[0237] S1. Preparation of the precursor solution: The transition metal source and inorganic phosphoric acid are dissolved and mixed, acid is added to adjust the pH of the solution, and heating is used to promote the dissolution of the transition metal source, thus obtaining the precursor solution. Specifically, the pH range is 2, and the heating temperature range is 565℃.
[0238] S2. Preparation of the pre-oxidized precursor solution: Hydrogen peroxide is added to the above precursor solution to oxidize the divalent metal ions in the solution to trivalent ions, generating the pre-oxidized precursor solution. Specifically, the amount of hydrogen peroxide added is 1.1 times the molar amount of the metal element in the transition metal source.
[0239] S3. Preparation of preprecipitated precursor slurry: The above-mentioned pre-oxidized precursor solution is heated to boiling to remove volatile acids, generating a preprecipitated precursor slurry. Specifically, the heating and boiling temperature range is 100℃.
[0240] S4. Preparation of neutral precursor slurry: The pre-precipitated precursor slurry is neutralized with an alkali metal sodium source to generate a neutral precursor slurry. Specifically, the neutralization condition is that the pH range of the slurry reaches 7.
[0241] S5. Solid-liquid separation: The neutral precursor slurry is dried to achieve solid-liquid separation, thus obtaining the precursor powder for polyanionic cathode materials. Specifically, the neutral slurry is dried by spray drying.
[0242] In this comparative example, the inorganic phosphoric acid is phosphoric acid and pyrophosphoric acid. The acidic solutions with the specified pH are formic acid and acetic acid. The transition metal source is an iron source, specifically elemental iron and iron oxide. The alkali metal sodium source is sodium hydroxide, sodium oxide, and sodium peroxide.
[0243] This comparative example also provides a method for preparing a positive electrode active material, including:
[0244] Add the above Na to deionized water 0.64 Fe 0.72 H 0.2 The raw material system was prepared by mixing PO4 precursor, sodium acetate, manganese sulfate, titanium sulfate Ti(SO4)2, and glucose. The raw material system was then ball-milled in a high-speed ball mill to obtain a precursor solution.
[0245] The precursor solution was then spray-dried and sintered in flowing argon gas to obtain the positive electrode active material Na4Mn. 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C.
[0246] Comparative Example 5
[0247] This comparative example is basically the same as Example 1, except that: in the preparation process of the positive electrode active material precursor, Ti(SO4)2 and MnSO4 are used to replace MnSO4, and the molar ratio of sodium, manganese, titanium, iron and phosphorus in the positive electrode active material precursor is 1.85:0.02:0.02:2.94:5.42.
[0248] In the preparation process of the positive electrode active material, FePO4 is added to the raw material system, and the chemical formula of the positive electrode active material is Na4Mn. 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C.
[0249] Comparative Example 6
[0250] This comparative example is basically the same as Example 1, except that: in the preparation process of the positive electrode active material precursor, Ti(SO4)2 and MnSO4 are used to replace MnSO4, and the molar ratio of sodium, manganese, titanium, iron and phosphorus in the positive electrode active material precursor is 1.85:0.02:0.02:2.94:3.14;
[0251] In the preparation process of the positive electrode active material, NH4H2PO4 is added to the raw material system, and the chemical formula of the positive electrode active material is Na4Mn. 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C.
[0252] Comparative Example 7
[0253] This comparative example is basically the same as Example 1, except that: in the preparation process of the positive electrode active material precursor, Ti(SO4)2 and MnSO4 are used to replace MnSO4, and the molar ratio of sodium, manganese, titanium, iron and phosphorus in the positive electrode active material precursor is 1.85:0.02:0.02:1.06:1.23;
[0254] In the preparation process of the positive electrode active material, FePO4 and NH4H2PO4 are added to the raw material system. The chemical formula of the positive electrode active material is Na4Mn. 0.02 Ti 0.02 Fe 2.94 (PO4)2P2O7@C.
[0255] Comparative Example 8
[0256] This comparative example is basically the same as Example 1, except that: in the preparation process of the positive electrode active material precursor, Ti(SO4)2 and MnSO4 are used to replace MnSO4, and the molar ratio of sodium, manganese, titanium, iron and phosphorus in the positive electrode active material precursor is 1.85:0.3:0.2:2.48:4.
[0257] The chemical formula of the positive electrode active material is Na4Mn 0.3 Ti 0.2 Fe 2.48 (PO4)2P2O7@C.
[0258] Experimental Example 1
[0259] The following parameters of the amorphous positive electrode active material precursor and positive electrode active material of each embodiment and comparative example were tested:
[0260] 1) Chemical composition: ICP test method was used, and the results are shown in Table 1 and Table 2;
[0261] 2) XRD patterns: Compare the ratio of the diffraction peak intensity at 33.5°–34° to that at 32.6°–33.4° in the XRD patterns of the positive electrode active material. Figure 1 The images show the XRD patterns of the amorphous positive electrode active material precursors of Examples 5 and Comparative Examples 1-3. Figure 2 XRD patterns of the positive electrode active material precursors of Example 5 and Comparative Examples 1-3;
[0262] 3) Electron micrograph: see Figure 3 and Figure 5
[0263] 4) Element distribution map: see Figure 4 .
[0264] The test results are shown in Table 1.
[0265] Table 1. ICP test results of the positive electrode active material precursor in Example 5
[0266]
[0267] Note: The normalization in Table 1 refers to the molar amount of other atoms calculated when the molar amount of phosphorus atoms in the positive electrode active material precursor is set to 4.000.
[0268] Table 2. Parameters of the positive electrode active material precursors (precursors) for each embodiment and comparative example.
[0269]
[0270]
[0271] Table 3
[0272]
[0273]
[0274]
[0275] Data Analysis:
[0276] Figure 1The XRD patterns of the positive electrode active material precursors of Example 5 and Comparative Examples 1-3 are shown. The XRD patterns of the positive electrode active material precursors of other examples are similar to those of Example 5, and there are no obvious diffraction peaks, indicating that the positive electrode active material precursors of each example are amorphous.
[0277] The XRD patterns of all examples and Comparative Example 1 (undoped) showed no obvious diffraction peaks, indicating that doping does not affect the amorphous state of the precursor. The XRD pattern diffraction peaks of Comparative Example 2 were consistent with the Joint Committee on Powder Diffraction Standards (JCPDS) data (PDF#86-1656), indicating that it was a precursor of ferric hydrogen phosphate. The XRD pattern diffraction peaks of Comparative Example 3 were consistent with the JCPDS data (PDF#84-0876), indicating that it was a precursor of ferric hydrogen phosphate.
[0278] Figure 2 The XRD patterns of the cathode active material precursors of Example 5 and Comparative Examples 1-3 are shown. The XRD pattern diffraction peaks of the cathode active material of Example 5 are consistent with the JCPDS data (PDF#01-086-4091), and the crystal structure is a triclinic P-1 type space group. Among them, the impurity peak intensity of NaFePO4 at around 33° in Comparative Examples 2-3 is significantly higher than that in Comparative Example 1, indicating that ball milling of the amorphous precursor can reduce the impurity phase content in the material. The impurity peak intensity of NaFePO4 at around 33° in Comparative Example 1 is significantly higher than that in Example 5, indicating that the A source and ball milling of the amorphous precursor are not conducive to the transport of dopant ions, resulting in uneven ion distribution in the material, thus resulting in a higher NaFePO4 impurity phase content in Comparative Example 1.
[0279] Figure 9 for Figure 2 A magnified XRD pattern of the red area in the middle, from Figure 9 It can be seen that, compared with Comparative Examples 1-3, the main peak in Example 5, which was around 33.7°, shifted to a lower angle. The cell size of NFPP increased according to the Bragg equation, and the larger cell size promoted sodium ion transport, thereby improving the electrochemical performance of the material. Due to Ti... 2+ The ionic radius of (0.086 nm) is greater than that of Fe. 2+ The large (0.078nm) value indicates that Ti, as a partial substitute for Fe, was successfully doped into the NFPP crystal (Mn). 2+ The ionic radius is comparable to that of Fe, which cannot be proven by the shift of the main peak in XRD.
[0280] Depend on Figure 3 It can be seen that the Mn prepared in Example 5 0.02 Ti 0.02The morphology of the doped amorphous precursor and the amorphous precursor prepared in Comparative Example 1 are not much different, indicating that a small amount of doping does not affect the surface morphology of the precursor. However, the FePO4·2H2O precursor particles in Comparative Example 3 are significantly larger than the precursors in Example 5 and Comparative Examples 1-2.
[0281] Depend on Figure 4 As shown in Table 1, the Mn prepared in Example 5 0.02 Ti 0.02 The relatively uniform elemental distribution in the doped amorphous precursor indicates that a uniform dopant ion distribution can be achieved in the doped ferric hydrogen phosphate precursor, and the dopant ions do not need to undergo a difficult diffusion process during sintering. The elemental distribution in the amorphous precursors of other embodiments is also relatively uniform, similar to Example 5.
[0282] Depend on Figure 5 It can be seen that the morphology of the positive electrode active materials prepared in Example 5 and Comparative Example 1 is not much different, indicating that the doping occurring during precursor synthesis or ball milling does not affect the surface morphology of the positive electrode active materials. Compared with Comparative Examples 2-3, the positive electrode active materials prepared in Example 5 and Comparative Example 1 have better primary particle fusion and blurred boundaries between particles, indicating that the amorphous precursor provided by the present invention can achieve good particle fusion during ball milling, thereby reducing the generation of impurity phases in the material. The secondary particle size of the positive electrode active material is significantly smaller, which can give the positive electrode active material better rate performance. The primary particles of the positive electrode active material prepared in Comparative Example 3 are significantly smaller than those in Comparative Example 2, indicating that the precursor of the positive electrode active material is ball-milled more thoroughly. However, the positive electrode active material prepared in Comparative Example 3 still has a lot of impurity phases, indicating that the micron- or submicron-level mixing during ball milling still requires a difficult diffusion process and cannot make the ions in the positive electrode active material completely uniform.
[0283] Experimental Example 2
[0284] The positive electrode active material, conductive agent - carbon black, and polyvinylidene fluoride (PVDF) of the above embodiments and comparative examples were added to the solvent N-methylpyrrolidone (NMP) in a weight ratio of 8:1:1, and then stirred in a vacuum mixer to form a stable and uniform battery slurry. The above positive electrode slurry was coated on the current collector - aluminum foil and dried at 105°C for 6 hours to obtain the positive electrode sheet. Then, a metal sodium sheet of suitable size was cut as the negative electrode sheet. Then, 1 mol of sodium hexafluorophosphate (NaPF6) was dissolved in 1 L of organic solvent (the organic solvent included propylene carbonate and fluoroethylene carbonate in a ratio of 100:6) to obtain the electrolyte. Then, in a glove box under an argon atmosphere, the above positive electrode sheet, the separator - glass fiber separator, and the above negative electrode sheet were alternately stacked and injected with the above electrolyte to assemble a CR2032 coin cell.
[0285] The aforementioned button cells were left to stand at 25°C for 12 hours and then tested on a Land-2001A battery testing system. Each cell underwent charge-discharge cycle testing and rate performance testing at 25°C, with a voltage range of 2V-4V. Specifically, the discharge specific capacity and capacity retention rate after 200 cycles at 1C were tested, as well as the discharge specific capacity at 5C and the percentage of the discharge specific capacity at 5C to that at 0.1C. The results are shown in Table 4. The capacity retention rate after 200 cycles is equal to the ratio of the discharge capacity after 200 cycles to the discharge capacity of the first cycle. The capacity retention rate for other cycle numbers can be interpreted in the same way. The discharge specific capacity of the first cycle is equal to the ratio of the discharge capacity of the button cell in the first cycle to the weight of the positive electrode material in the battery.
[0286] Furthermore, the charge-discharge curves of the batteries prepared using the positive electrode active materials of Example 5 and Comparative Examples 1-3 at 0.1C are shown below. Figure 6 As shown, the cycle performance of batteries prepared using the positive electrode active materials of Example 5 and Comparative Examples 1-3 at 1C is illustrated in the graph. Figure 7 As shown, the discharge specific capacity test graphs of the batteries prepared using the positive electrode active materials of Example 5 and Comparative Examples 1-3 at 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C rates are shown in the figure. Figure 8 As shown.
[0287] Table 4
[0288]
[0289]
[0290] Data Analysis:
[0291] Analysis of Examples 1, 2, 3, 5, 8, 10, 11, 13, 14, and 18-23 shows that the doping element A in the positive electrode active material precursor includes one or more of Cr, Zr, Nb, Cu, V, Ti, and Zn, which helps to further improve the cycle performance, rate performance, and charge / discharge specific capacity of the battery.
[0292] Comparative Example 1, which is not doped with metal elements, has poor cycle performance, rate performance, and charge / discharge specific capacity.
[0293] Analysis of the various embodiments and comparative examples 2-4 shows that the positive electrode active material precursor of the present invention helps to further improve the cycle performance, rate performance and charge / discharge specific capacity of the battery.
[0294] Analysis of Example 1 and Comparative Examples 5 and 6 shows that controlling 0.60≤(x+y) / z≤0.90 helps to improve the battery's cycle performance, rate performance, and charge / discharge specific capacity.
[0295] Analysis of Example 1 and Comparative Examples 7 and 8 shows that controlling 0 < w / z ≤ 1.1 and 0 < y / x ≤ 0.15 helps to improve the cycle performance, rate performance and charge / discharge specific capacity of the battery.
[0296] Depend on Figure 6 It can be seen that the batteries prepared using the positive electrode active materials of Example 5 and Comparative Examples 1-3 exhibit two discharge plateaus at approximately 2.79V and 3.2V during 0.1C charge-discharge, indicating that the Na in the batteries... + The insertion / extraction reaction was a single-phase reaction, with a discharge plateau of around 2.67V in the impure phase NaFePO4. The order of significance was: Comparative Example 3 > Comparative Example 2 > Comparative Example 1 > Example 5, which is consistent with the XRD results.
[0297] Depend on Figure 7 It can be seen that, after 200 cycles at 1C rate, the discharge specific capacity of Example 5 was 97.04 mAh / g, and the battery capacity retention rate was 99.82%; the discharge specific capacity of Comparative Example 1 after 200 cycles at 1C rate was 94.63 mAh / g, and the battery capacity retention rate was 99.41%; the discharge specific capacity of Comparative Example 2 after 200 cycles at 1C rate was 93.22 mAh / g, and the battery capacity retention rate was 99.34%; the discharge specific capacity of Comparative Example 3 after 200 cycles at 1C rate was 84.63 mAh / g, and the battery capacity retention rate was 95.27%. This shows that the battery prepared with the cathode material prepared in Example 5 has excellent cycle performance.
[0298] Depend on Figure 8 It can be seen that at discharge rates of 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C, the discharge specific capacities of Example 5 are 101.46, 100.30, 98.43, 97.22, 95.82, and 93.83 mAh / g, respectively; the discharge specific capacities of Comparative Example 1 are 98.85, 97.92, 96.29, 95.15, 93.67, and 91.02 mAh / g, respectively; the discharge specific capacities of Comparative Example 2 are 97.03, 96.53, 95.05, 93.80, 92.12, and 89.17 mAh / g, respectively; and the discharge specific capacities of Comparative Example 3 are 94.45, 93.31, 91.48, 88.82, 86.35, and 84.23 mAh / g, respectively. Example 5 showed a discharge specific capacity of 92.47% at 5C and 0.1C, Comparative Example 1 showed a discharge specific capacity of 92.07% at 5C and 0.1C, Comparative Example 2 showed a discharge specific capacity of 91.90% at 5C and 0.1C, and Comparative Example 3 showed a discharge specific capacity of 89.18% at 5C and 0.1C. This indicates that the battery prepared from the cathode material of Example 5 has good high-rate performance.
[0299] As can be seen from Table 4, compared with Comparative Examples 1-3, the high-rate performance and cycle performance of Examples 1-9 are significantly improved. It can be seen that by adding the metal doping source (A source) to the reaction solution for preparing the amorphous precursor in Examples 1-9, the distribution uniformity of metal doping ions in the amorphous precursor can be effectively improved, thereby effectively improving the electrochemical performance of the battery.
[0300] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A positive electrode active material precursor, characterized in that, The chemical formula of the positive electrode active material precursor is Na. w Fe x A y P z O m Where 0.60≤(x+y) / z≤0.90, 0<w / z≤1.1, 0<y / x≤0.15, and m satisfies Na w Fe x A y P z O m It is electrically neutral, and A is a metallic element.
2. The positive electrode active material precursor according to claim 1, characterized in that, 0.67≤(x+y) / z≤0.
75.
3. The positive electrode active material precursor according to claim 1 or 2, characterized in that, 0.1 < w / z ≤ 1.
0.
4. The positive electrode active material precursor according to any one of claims 1-3, characterized in that, 0 < y / x ≤ 0.
04.
5. The positive electrode active material precursor according to claim 4, characterized in that, 3.5 < m / z ≤ 4.
0.
6. The positive electrode active material precursor according to any one of claims 1-5, characterized in that, The positive electrode active material precursor is amorphous.
7. The positive electrode active material precursor according to any one of claims 1-6, characterized in that, The sum of the mass percentages of Na, Fe, A, and P elements in the positive electrode active material precursor is 45% to 60%.
8. The positive electrode active material precursor according to any one of claims 1-7, characterized in that, In the precursor of the positive electrode active material, element A replaces some of the positions of element Fe in the lattice of the precursor of the positive electrode active material.
9. The positive electrode active material precursor according to claim 8, characterized in that, A includes one or more of Cr, Zr, Nb, Cu, V, Ti, and Zn.
10. The positive electrode active material precursor according to any one of claims 1-9, characterized in that, The Fe element in the positive electrode active material precursor is in the trivalent state.
11. The positive electrode active material precursor according to any one of claims 1-10, characterized in that, The positive electrode active material precursor also contains water of crystallization.
12. A method for preparing a positive electrode active material precursor according to any one of claims 1-11, characterized in that, include: The precursor of the positive electrode active material is prepared by mixing and reacting a first raw material system comprising an iron source, a first sodium source, an A source, a phosphorus source, and an oxidant.
13. The method for preparing the positive electrode active material precursor according to claim 12, characterized in that, Also includes: The pH value of the first raw material system, which includes an iron source, a first sodium source, an A source, a phosphorus source, and an oxidant, is adjusted to 2-6. Then, the first raw material system is reacted to obtain the positive electrode active material precursor.
14. The method for preparing the positive electrode active material precursor according to claim 12 or 13, characterized in that, Also includes: After the reaction is completed, the reaction system is aged for 0.5 to 3 hours, and then the product in the reaction system is washed 1 to 6 times to obtain the positive electrode active material precursor.
15. The method for preparing the positive electrode active material precursor according to any one of claims 12-14, characterized in that, The iron source includes one or more of ferrous sulfate, ferrous oxalate, iron powder, iron oxide, and ferric nitrate. And / or, the first sodium source includes one or more of sodium dihydrogen phosphate, sodium acetate, sodium pyrophosphate, sodium carbonate, sodium oxalate, and disodium hydrogen phosphate; And / or, the phosphorus source includes one or more of the following: ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium pyrophosphate, disodium hydrogen phosphate, and phosphoric acid; And / or, the A source includes one or more of the following: metal oxides, metal salts, and organometallic compounds of Cr, Zr, Nb, Cu, V, Ti, and Zn; And / or, the oxidant includes a peroxide, which includes hydrogen peroxide.
16. A positive electrode active material, characterized in that, The positive electrode active material is formed from the positive electrode active material precursor according to any one of claims 1-11 or the positive electrode active material precursor prepared according to the preparation method according to any one of claims 12-15.
17. The positive electrode active material according to claim 16, characterized in that, The lattice structure of the positive electrode active material is a triclinic crystal system with a space group of type P-1. And / or, in the X-ray diffraction pattern, the ratio of the diffraction peak intensity of the positive electrode active material at 33.5°–34° to the diffraction peak intensity at 32.6°–33.4° is 10–18; And / or, the positive electrode active material further includes a carbon coating layer present on at least a portion of the surface of the positive electrode active material.
18. A method for preparing the positive electrode active material according to claim 16 or 17, characterized in that, include: The positive electrode active material is obtained by sintering a second raw material system comprising the positive electrode active material precursor according to any one of claims 1-11.
19. The method for preparing the positive electrode active material according to claim 18, characterized in that, The second raw material system also includes a second sodium source, which includes one or more of sodium dihydrogen phosphate, sodium acetate, sodium pyrophosphate, sodium carbonate, sodium oxalate, and disodium hydrogen phosphate. And / or, the second raw material system further includes a carbon source, said carbon source including one or more of glucose, ascorbic acid, oxalic acid, citric acid, fructose, and sucrose; And / or, the sintering temperature is 450–600°C.
20. A secondary battery, characterized in that, The device includes a positive electrode sheet, which includes a positive current collector and a positive active material layer disposed on the positive current collector, wherein the positive active material layer includes the positive active material as described in claim 16 or 17.
21. An electrical appliance, characterized in that, The device includes the secondary battery as described in claim 20, wherein the secondary battery serves as the power supply for the electrical equipment.
Citation Information
Patent Citations
Preparation method and application of battery-grade iron hydrogen phosphate
CN116924369A
Polyanionic sodium ion battery positive electrode material precursor and preparation method thereof
CN118479443A